EU law beyond EU borders : the extraterritorial reach of EU law - Cremona, Marise; Scott, Joanne (Oxford : Oxford University Press, 2019)
Analysing the impact of EU law beyond its borders, this book examines the use of law as a powerful instrument of EU external action and addresses some of the normative challenges this poses. The 'global reach' of EU law is examined in policy areas of the environment, the internet and data protection, banking and financial markets, competition policy and migration.
Previously issued in print: 2019.
Includes index.
Specialized.
Description based on online resource; title from home page (viewed on May 16, 2019).
Keywords: Law -- European Union countries -- International unification; International and municipal law -- European Union countries; Law and globalization -- European Union countries; Law; International law